FTIR studies of chemical processes - Few, J; Julian Few (2013)
This thesis presents the study of a selection of gas phase chemical processes using time-resolved Fourier transform infrared (FTIR) emission spectroscopy. Such processes include molecular energy transfer, chemical reaction and photodissociation. The major focus of this thesis was the investigation of collisional energy transfer from the electronically excited states of NO and OH, with particular attention paid to the fate of the electronic energy. NO A2Σ+(v = 0) is prepared by laser excitation, pumping the overlapped Q1 and P21 band heads of the NO A-X (0,0) transition at 226.257 nm. The quenching of this state by O2 and CO2 was studied. Experiments were performed to investigate what channels contribute to the quenching process, the branching ratio of these different channels and the partitioning of energy among the various products. Quenching by O2 was found to proceed mostly through non-reactive channels. High vibrational excitation of NO X 2Π was observed, with population detected in v = 22, representing 79% of the available energy. The O2 product was found to be formed in more than one electronic state: the ground state, X 3Σ-g, and a high-lying electronically excited state, such as the A 3Σ+u, A' 3Δu or c 1Σ-u states. A reactive channel producing vibrationally excited NO2 was observed, but was found to be a minor process with an upper limit of 18% for the branching ratio. In contrast the quenching of NO A 2Σ+(v = 0) by CO2 was found to proceed predominately by reaction, with a branching ratio of 76 %. While emission from NO2 was observed, it was weak, and therefore it was concluded that the main reaction products were CO, O(3P) and NO X 2Π(v = 0). The nascent strong CO2 v3 emission band from the non-reactive channel exhibited a large red-shift from its fundamental position. This indicates that the CO2 vibrational distribution is significantly hotter than statistical. Investigations were then performed studying the quenching of NO A 2Σ+(v = 1) by NO and CO2, with both systems exhibiting similar characteristics to the quenching of the ground vibrational level of NO A 2Σ+. From comparison of the emission intensity of the CO fundamental and CO2 v3 mode following quenching of the v = 0 and 1 levels of the NO A 2Σ+ state, it was concluded that the branching ratio for reactive quenching was larger in the latter case. Secondly, experiments were performed to measure the rate constants for the quenching of NO A 2Σ+(v = 0) by the noble gases. The noble gases are inefficient quenchers of electronically excited NO and therefore careful experimental design was required to minimise the influence of impurities on the results. All the rate constants were found to be of the order of 10-14 cm3 molecule-1 s-1. The value for Xe was 50 times smaller than reported previously in the literature. In light of this new measurement, a re-analysis of experiments, performed previously in the group, on the electronic quenching of NO A 2Σ+(v = 0) by Xe was performed. A very hot vibrational distribution of NO X 2Π was obtained. Next, the collisional quenching of OH A 2Σ+(v = 0) by H2 was investigated. OH radicals were generated in situ by the photolysis of HNO3 at 193 nm, which were excited to the A 2Σ+(v = 0) state on the overlapped Q1(1) and P21(1) rotational lines at 307.935 nm. Reactive quenching was found to be the major pathway, in agreement with the literature. Copious emission from vibrationally excited water was observed. Comparison of this emission with theoretical calculations revealed a hotter distribution than predicted. It was concluded that the energy channelled into the vibrational modes of H2O is in excess of 60% of the available energy. Experiments performed with D2 allowed the non-reactive channel to be studied; a cold vibrational distribution of the OH X 2Π was observed. Finally the reaction between CN radicals and cyclohexane was studied. CN was generated by the photolysis of ICN at 266 nm. Prompt emission from HCN in the C-H stretching region was observed meaning the new bond was formed in a vibrationally excited state. Analysis of the emission revealed HCN was populated up to v3 = 2. Excellent agreement with the results of a theoretical study of the system was found.